Effectiveness of service models and organisational structures supporting tuberculosis identification and management in hard-to-reach populations in countries of low and medium tuberculosis incidence: a systematic review. Issue 9 (8th September 2018) - Heuvelings, Charlotte C; Greve, Patrick F; de Vries, Sophia G; Jelle Visser, Benjamin; Bélard, Sabine; Janssen, Saskia; Cremers, Anne L; Spijker, René; Shaw, Elizabeth; Hill, Ruaraidh A; Zumla, Alimuddin; Sandgren, Andreas; et al.
Abstract : Objective: To determine which service models and organisational structures are effective and cost-effective for delivering tuberculosis (TB) services to hard-to-reach populations. Design: Embase and MEDLINE (1990–2017) were searched in order to update and extend the 2011 systematic review commissioned by National Institute for Health and Care Excellence (NICE), discussing interventions targeting service models and organisational structures for the identification and management of TB in hard-to-reach populations. The NICE and Cochrane Collaboration standards were followed. Setting: European Union, European Economic Area, European Union candidate countries and Organisation for Economic Co-operation and Development countries. Participants: Hard-to-reach populations, including migrants, homeless people, drug users, prisoners, sex workers, people living with HIV and children within vulnerable and hard-to-reach populations. Primary and secondary outcome measures: Effectiveness and cost-effectiveness of the interventions. Results: From the 19 720 citations found, five new studies were identified, in addition to the six discussed in the NICE review. Community health workers from the same migrant community, street teams and peers improved TB screening uptake by providing health education, promoting TB screening and organising contact tracing. Mobile TB clinics, specialised TB clinics and improved cooperation between healthcare services can be effective at identifying and treating active TB cases and are likely to be cost-effective. No difference in treatment outcome was detected when directly observed therapy was delivered at a health clinic or at a convenient location in the community. Conclusions: Although evidence is limited due to the lack of high-quality studies, interventions using peers and community health workers, mobile TB services, specialised TB clinics and improved cooperation between health services can be effective to control TB in hard-to-reach populations. Future studies should evaluate the (cost-)effectiveness of interventions on TB identification and management in hard-to-reach populations and countries should be urged to publish the outcomes of their TB control systems. PROSPERO registration number: CRD42015017865.